2022
DOI: 10.3389/fpubh.2022.973832
|View full text |Cite
|
Sign up to set email alerts
|

Association between trace metals exposure and hearing loss

Abstract: BackgroundTrace metals have side-effect on human health. The association between trace metals exposure and hearing loss remains unclear.MethodsA total of 8,128 participants were exacted for analysis of association between trace metals and hearing loss from the database of the National Health and Nutrition Examination Survey (NHANES) (2013–2018). Multivariable logistic regression and restricted cubic spline models were used to examine the association between trace metals and hearing loss.ResultsParticipants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It enhanced our understanding of the data and provided a more precise basis for scientific insight. This study covered 15 studies published between 2009 and 2022, 11 of which were conducted in Asia (Japan, 6,11,12 Korea, 3,9,13,14 and China 5,7,15,16 ) and 4 in the United States. 4,[17][18][19] Of these studies, 10 articles identified lead and cadmium as the main or one of the risk factors for HL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It enhanced our understanding of the data and provided a more precise basis for scientific insight. This study covered 15 studies published between 2009 and 2022, 11 of which were conducted in Asia (Japan, 6,11,12 Korea, 3,9,13,14 and China 5,7,15,16 ) and 4 in the United States. 4,[17][18][19] Of these studies, 10 articles identified lead and cadmium as the main or one of the risk factors for HL.…”
Section: Discussionmentioning
confidence: 99%
“…20 Clinically, HL is typically defined as an average pure-tone threshold exceeding 25 decibels. 5 Given the widespread ubiquity of heavy metal exposure, it is critical to investigate and recognize the relationship between environmental heavy metal exposure and the risk of HL. This meta-analysis and review aim to comprehensively examine the association between heavy metals, including lead, cadmium, mercury, arsenic, barium, and manganese, and the incidence of HL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hearing loss is determined by affirmative responses to the question: Are you deaf or do you have serious difficulty hearing? [25] Diabetes is determined according to the answer to the following question: Other than during pregnancy, have you/has SP ever been told by a doctor or health professional that you have/he/she/SP has diabetes or sugar diabetes?…”
Section: Assessment Of Hearing Loss and Diabetesmentioning
confidence: 99%